Trend, determinants, and future prospect of child marriage in the Amhara region, Ethiopia: a multivariate decomposition analysis - Anteneh Mengist Dessie; Denekew Tenaw Anley; Melkamu Aderajew Zemene; Natnael Atnafu Gebeyehu; Getachew Asmare Adella; Gizachew Ambaw Kassie; Misganaw Asmamaw Mengstie; Mohammed Abdu Seid; Endeshaw Chekol Abebe; Molalegn Mesele Gesese; Kirubel Dagnaw Tegegne; Rahel Mulatie Anteneh; et al. (Frontiers Media S.A., 2023)
BackgroundChild marriage is a harmful traditional practice, which compromises children of their childhood and threatens their lives and health. In Ethiopia, 58% of women and 9% of men get married before the age of 18 years. Surprisingly, parents in the Amhara region make marriage promises of their children before they are even born, which will hinder the region from attaining the Sustainable Development Goal of ending child marriage. Thus, this study aimed to assess the trends, determinants, and future prospects of child marriage in the Amhara region of Ethiopia.MethodsA repeated cross-sectional study was conducted using four consecutive nationally representative Ethiopian demographic and health surveys (2000-2016). A logit-based multivariate decomposition analysis for a non-linear response model was fitted to identify factors that contributed to the change in child marriage over time. Statistical significance was declared at a p-value of < 0.05. The child marriage practice in the Amhara region by the year 2030 was also predicted using different forecasting features of Excel.ResultsThe trend of child marriage over the study period (2000-2016) decreased from 79.9% (76.7, 82.8) to 42.9% (39.1, 46.9), with an annual average reduction rate of 2.9%. Approximately 35.2% of the decline resulted from an increase in the proportion of women who attained secondary and above-secondary education over the two surveys. A decrease in the proportion of rural women and a change in the behavior of educated and media-exposed women also contributed significantly to the decline in child marriage. The prevalence of child marriage in the Amhara region by the year 2030 was also predicted to be 10.1% or 8.8%.ConclusionThough there has been a significant decline in child marriage in the Amhara region over the past 16 years, the proportion is still high, and the region is not going to eliminate it by 2030. Education, residence, and media exposure were all factors associated with the observed change in child marriage in this study. Therefore, additional efforts will be required if child marriage is to be eliminated by 2030, and investing more in education and media access will hasten the region's progress in this direction.